Autonomy, sovereignty, and self-determination : the accommodation of conflicting rights - Hannum, Hurst (Procedural aspects of international law series., 1996)
Demands for "autonomy" or minority rights have given rise to conflicts, often violent, in every region of the world and under every political system. Through an analysis of contemporary international legal norms and an examination of several specific case studies - including Hong Kong, India, the transnational problems of the Kurds and Saamis, Nicaragua, Northern Ireland, Spain, Sri Lanka, and the Sudan - this book goes beyond mere slogans and identifies a framework in which ethnic, religious, and regional conflicts can be addressed. This newly revised edition includes two new chapters which expand and update both the topical discussions and the case studies included in the first edition.